Geomagnetic pulsation over conjugate locations during geomagnetic storms and substorm - Selvamurugan, R.; Pathan, B. M.; Hanchinal, A. N.; Dhar, Ajay (My University, 2011)
Geomagnetic data collected during magnetic storm over magnetically conjugate pair (according to IGRF 2000) of high latitude stations viz., Maitri (70 450 S, 11 420 E) and Tromso (69 400 N, 18 560 E) reveal that amplitudes of Pc6 pulsation characteristically differ. The amplitude obtained from horizontal magnetic field for the Pc6 pulsation frequency range between 0.6 and 1.6 mHz significantly differs in time corresponding to peak amplitude. The relative differences in its time of occurrence found to gradually increase around initial phase of storm and remain exactly out of phase at peak amplitude of storm. Thence, it is found to be in agreement in phase gradually until storm unwinds. This indicates that simultaneous amplitude of Pc6 pulsation at conjugate pair of stations and its time of occurrence could be a key factor to infer storm arrivals somewhat prior to its peak effects. The emphasize remains on prediction of storm arrivals only by utilizing ground based magnetometer observations. However, it is necessary to understand differences on the basis of weak, moderate, strong, and super strong cases and more exactly how they behave along the line of magnetic Meridian. Nevertheless, the analysis implies that geo-effective magnetic ejecta/clouds/CIRs/sheaths/CMEs/ICMEs giving rise to geomagnetic storm can be predicted ahead of its peak effects by having magnetometer data over conjugate locations.
Keywords: Geomagnetic storms; Space weather; Magnetic pulsations; Storms; Substorms